Association of CETP polymorphisms with the risk of vascular dementia and white matter lesions - Qureischie, Homeira; Heun, R.; Popp, J.; Jessen, F.; Maier, W.; Schmitz, S.; Hentschel, Frank; Kelemen, Peter; Kölsch, H. (Journal of neural transmission, 2009)
Cholesteryl ester transfer protein (CETP), a component of the high density lipoprotein (HDL), plays a central role in reverse cholesterol transport. We investigated the association of two putative functional CETP polymorphisms (C-629A and I405V) with the risk of vascular dementia (VD) and tested if this association is influenced by the presence of APOE4 allele. Our study included 163 VD patients (mean age: 74.25 ± 7.9 years) and 452 cognitively healthy probands (mean age: 70.81 ± 7.9 years). As a biological correlate, the association of CETP gene variants with white matter lesion (WML) load was investigated. Neither the C-629A (P = 0.169) nor the I405V (P = 0.840) polymorphism was associated with VD risk in the whole sample. However, in non-carriers of the APOE4 allele, homozygote carriers of the CETP C-629A A allele presented with an increased risk of VD (P = 0.01). Whereas in APOE4 carriers, no association of CETP polymorphisms with VD risk was detected. In addition, carriers of the CETP C-629A AA genotype presented with decreased WML load in the frontal brain (P = 0.009). Our results suggest that CETP gene polymorphisms might influence WML load and the risk of VD, the latter in non-carriers of the APOE4 allele.
Gesehen am 15.10.2020